Information and communication technology and quality in public management - Alponte Montoya, Alvaro Esteban (2022)
The general objective was to determine to what extent information and communication technology is related to public management, from the perception of employees, in the Regional Government of Tacna, 2020. The following methodology was used: the present investigation is Pure, with a non-experimental and transectional design. The survey technique was administered to the workers of the sample under study, in order to know their perception of information and communication technology and public management, in the Regional Government of Tacna, in order to establish their relationship. The population is made up of 335 employees, applying the systematic random sampling method to 180 of the workers. The main conclusion was that information and communication technology is related to public management directly for the employees of the Regional Government of Tacna, however; the significance level <0.05 reached allows determining that the relationship of information and communication technology with public management is moderate. Based on the fact that the Regional Government of Tacna has the financial means to be able to make good use of human and technological resources, we need them to see the need to improve their service.